Analysis of Factors Affecting the Adaptation Ability of Employees of Aviation Navigation Companies in Indonesia - Riyansah, Muhammad; Marnisah, Luis; Rekarti, Endi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
At this time, apart from aviation safety being the main priority, the world of aviation is required to be safer, more efficient, more cost-effective, and able to increase economic growth and reduce environmental impacts. AirNav Indonesia as the only provider of aviation navigation services in Indonesia must be able to adapt to changes supported by human resource capabilities. Therefore, the role of education and training, career development, and agility can encourage the emergence of employee adaptability. This research took a sample of 125 employees at the AirNav Indonesia company, Palembang Branch Office. The collection was carried out using a non-probability sampling method. Variable measurement was carried out using a Likert scale. Data analysis shows that the education and training and agility variables have a positive and significant effect on adaptability, while the career development variable is not proven to have an effect on adaptability.